Comparative analysis of amoebic seropositivity among Kelantan cattle farm dwellers using CSA- and rCL-IgG-ELISA - Almazaraa, Khadeeja Ameen Khudhair (2021)
Kelantan cattle farm dwellers are one of the high-risk groups for invasive amoebiasis, as the farming activities involve the use of untreated water source such as underground and well water. Screening for invasive amoebiasis by crude soluble antigen (CSA) and recombinant c-terminal lectin (rCL) antigen provide different interpretation on the disease exposure. Assay based on the former antigen has higher affinity towards variety of anti-amoebic antibodies, while the latter is specific for invasive amoebiasis. The present study aimed to study the amoebic seropositivity among Kelantan cattle farm dwellers using customised CSA- and rCL-IgG-ELISA. The two different antigens were produced and used for the screening of the serum samples based on previously optimised parameters. Thirty blood donor serum samples were used for the determination of cut-off values for the two customised assays. RIDASCREEN® Entamoeba histolytica IgG was used as the reference test. From the analysis, the reference test detected 31 (34.83%) positive cases, while CSA- and rCL-IgG ELISA detected 41 (46.07%) and 17 (19.10%) cases, respectively. The two customised assays showed moderate agreement with the commercial test, nonetheless, CSA-ELISA showed higher agreement with the findings of commercial test, as compared to rCLELISA. From ROC curve analysis, the area under the curve of CSA-IgG-ELISA was higher than that of rCL-IgG-ELISA, as well. In conclusion, CSA- and rCL-IgG-ELISA showed different seropositivity; findings by the rCL-IgG-ELISA are lower and could be more specific for invasive amoebiasis.